2021
DOI: 10.1101/2021.01.15.21249681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Paradoxical Screening Serological Assay for the Diagnosis of Whipple’s Disease (infection with Tropheryma whipplei)

Abstract: Whipple’s disease (WD) is a rare infection due to Tropheryma whipplei. Following in-vitro cultivation of T. whipplei, an indirect-immunofluorescence serological assay (IFA) was developed. We tested the hypothesis that this assay could be used to either identify WD patients, or rule out WD, in patients in whom the diagnosis is being considered, based on the antibody titers of their IgM and IgG antibody responses. In this small study fourteen WD patients and 22 healthy volunteers’ sera were obtained from across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In this study, the level of thyroid autoantibodies in the experimental group was significantly higher than that in the control group before and after the treatment ( P < 0.001), despite a remarkable decline observed after the treatment ( P < 0.001), indicating the close relation between the occurrence and development of Graves' disease to thyroid autoantibodies and hormones that show great potential in the diagnosis of the disease. In the study by Liew et al, the positive rate of TRAb in diagnosing Graves' disease was 55% [ 32 ]. This study showed that the positive rate of the antibody in diagnosing Graves' disease was 60%.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the level of thyroid autoantibodies in the experimental group was significantly higher than that in the control group before and after the treatment ( P < 0.001), despite a remarkable decline observed after the treatment ( P < 0.001), indicating the close relation between the occurrence and development of Graves' disease to thyroid autoantibodies and hormones that show great potential in the diagnosis of the disease. In the study by Liew et al, the positive rate of TRAb in diagnosing Graves' disease was 55% [ 32 ]. This study showed that the positive rate of the antibody in diagnosing Graves' disease was 60%.…”
Section: Discussionmentioning
confidence: 99%